THE ISSUE OF CRAFTSMANSHIP IN THE FINANCIAL SYSTEM OF THE KOKAND KHANATE (World Bulletin of Public Health, 2024)
The article analyzes the financial system of the Kokand Khanate and issues of handicrafts in its development.
Keywords: Khan; money; tax; finance